Competing Motivations in Germany’s Higher Education Response to the “Refugee Crisis” - Streitwieser, Bernhard; Brück, Lukas (Refuge, 2018)
In 2015–16 Germany was confronted with over 1 million new refugees, which challenged public and private institutions alike and increasingly divided public sentiments. This article investigates the cultural, political, and economic dynamics as they were in Germany in 2015–16 and in particular how its higher education sector responded. The discussion covers a comprehensive review of media debates, public and private institutional research, new German- and English-language scholarship, and case studies the authors collected of fiffeen universities. The article ends with recommendations as German universities prepare for 30,000–50,000 refugees eligible for study in the coming years.